Determination of Total Mercury in The Water of Al-Kabeer AL-Shemaly River (Lattakia-SYRIA) (Latakia University Journal -Basic Sciences Series, 2019)
This study deals with the determination of total mercury concentration in the water taken from three sites on  Al-Kabeer Al-Shemaly River ( near the industrial area and Al-Damat Lake, and 16 Tishreen Lake), also the effect of some physio-chemical parameters  including: DO, pH, T °C. of water in the three sites was studied.Results showed that the total mercury concentration was low in general, where the medium concentration in the three studied sites was 0.29 ppb and it was less than the permission level of total mercury in the surface water(> 10 ppb), the higher value of the medium concentration of total mercury(0.35, 0.31, 0.21)ppb was recorded in the Industrial Area, Damat Lake, then 16 Tishreen Lake, respectively. For the changes in the total concentration of mercury in the three studied sites during seasons of a year, was higher in Summer comparing with other seasons. The results showed positive correlation coefficient between the total mercury concentration and temperature, pH value, but it was negative with DO in Summer.